Analisis Tingkat Kesadaran Masyarakat Dalam Pembayaran Zakat Pertanian (Studi Kasus Petani Di Desa Sidoharjo Kecamatan Tanjunganom Kabupaten Nganjuk) - Maulana, Ahmad (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2022)
Zakat has a transcendental and social dimension. It applies the principles of justice, balance and equity, also the benefits of people. In reality,people do not understand and know the implementation of agricultural Zakat. The research has some aims to determine the degree of awareness during the farmers implementing agriculture zakat in Sidoharjo,Tanjunganom subdistrict,Nganjuk regency. The case study of this research is “qualitative approach”.The techniques of data collection are observation,interview,documentation.While,the data analyses techniques used are reduction,presentation,and summary/verification data. Based on the result study,it can be cloncluded that the use and distribution of agricultural Zakat depend on the periodisation of both the harvest and Ramadan period.The Implementation of zakat can be in the form of money and material.zakat has the same meaning with infaq and sadaqah. This statement is not exacly and not accordance with shar’i rules. The farmers know about zakat but they don’t understand about agricultural zakat yet.The reason is due to that the awareness among farmers are low.Caused by the less understanding of the management Zakat,especially agricultural Zakat,low level of their educations,the distribution of Zakat is not yet on exactly target and unavailable Zakat management institution.